Development of Teacher Professional Development Package in Teaching Students with Special Needs in Inclusive Classrooms - Harnkajornsuk, Suthawan; Mitranun, Chanida; Wattanarat, Prapimpong; Vibulpatanavong, Kanokporn; Saksiriphol , Daranee; Khunchun, Patchareewan; Sirirak, Cheerapat; Boonyakarn, Tamala (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purpose of this research was to develop a teacher professional development package (TPDP) in the field of learning management for students with special needs in inclusive classes. This research was divided into 3 phases. Phase 1 teachers’ needs assessments on self-development in learning management for students with special needs. The sample group included 325 primary school teachers under the Bangkok Elementary Education Service Area Office, were obtained by stratified random sampling. Data was collected by using questionnaires and analyzed by using PNI modified Index. Phase 2: TPDP development using case-based learning. The informants consisted of 3 special education experts assessing the suitability of the TPDP kit. Data was analyzed by means and standard deviation. Phase 3: TPDP kit trial. The participants consisted of 17 teachers in elementary schools, tried the TPDP kit for 10 weeks. Data was analyzed by using descriptive statistics. The results showed that the TPDP kit consists of 5 areas: understanding of special needs characteristics; analysis of special needs learners in inclusive classroom; adjusting learning management methods; adjusting the learning environment; and adjusting learning assessment methods. The TPDP kit was effective in enhancing the teacher's ability to manage learning after using the TPDP kit higher than before using the TPDP kit.